(untitled) (Archives of Clinical Psychiatry, 2005)
Delirium is a neurobehavioral syndrome caused by the transient disruption of cerebral homeostasis, which is invariably subsequent to systemic or central nervous system insults. In general medical settings, the occurrence of delirium is also associated with a higher incidence of post-operative complications, longer hospital stays, and poor functional recovery. Ageing and cognitive decline are known risk factors for the occurrence of delirium. In elderly patients, delirium has been shown to be associated with pre-existing dementia. Conversely, non-demented elderly subjects who develop a new delirium episode display an increased incidence of dementia in the long-term outcome. Prospective case-control studies have demonstrated a significant association between the previous diagnosis of delirium and the development of dementia. The association between delirium and dementia may be even higher among the eldest elderly. After reviewing the relevant literature on the association between delirium and dementia, we hypothesize that the occurrence of delirium in non-demented elderly individuals is predictive of a worse cognitive outcome, and increased risk of dementia, in the long-term follow-up. We further discuss the biological nature of this association in the light of the cholinergic deficit observed in the pathophysiology of both delirium and Alzheimer's disease.